2020
DOI: 10.1128/aac.00414-20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Novel Pyrazolone Phosphodiesterase Inhibitors in Experimental Mouse Models of Trypanosoma cruzi

Abstract: Pyrazolones are heterocyclic compounds with interesting biological properties. Some derivatives inhibit phosphodiesterases (PDEs) and thereby increase the cellular concentration of cyclic AMP (cAMP), which plays a vital role in the control of metabolism in eukaryotic cells, including the protozoan Trypanosoma cruzi, the etiological agent of Chagas disease (CD), a major Neglected Tropical Disease. In vitro phenotypic screening identified a 4-bromophenyl-dihydropyrazole dimer as anti-T. cruzi hit and 17 novel py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“… 46 Ultrastructural analysis of drug-treated bloodstream trypomastigotes showed cellular changes consistent with autophagy and osmotic stress, mechanisms already previously linked to cAMP signaling as also observed for other PDE inhibitors. 42 , 43 , 44 , 45 , 46 Compound 9 raised both cellular and supernatant cAMP levels, confirming inhibition of T. cruzi PDE(s).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“… 46 Ultrastructural analysis of drug-treated bloodstream trypomastigotes showed cellular changes consistent with autophagy and osmotic stress, mechanisms already previously linked to cAMP signaling as also observed for other PDE inhibitors. 42 , 43 , 44 , 45 , 46 Compound 9 raised both cellular and supernatant cAMP levels, confirming inhibition of T. cruzi PDE(s).…”
mentioning
confidence: 67%
“…A greater anti-parasitic effect was observed against intracellular amastigotes (EC 50 values ranging from 0.17 to 3.3 µM on Tulahuen and Y strains) as compared to bloodstream trypomastigotes (Y strain). 44 Previous validation studies performed by the measurement of cAMP levels showed that untreated amastigotes have higher ability to efflux this second messenger than untreated bloodstream forms, which may influence, at least in part, the different susceptibility profile of trypomastigotes and amastigotes, as observed with the exposure of some PDE inhibitors. 42 , 44 The pyrazoles NPD-227 altered the morphology of bloodstream trypomastigotes inducing a rounding effect that impaired their invasion into the cardiac host cells, denoting that although not able to induce a rapid lysis, this pyrazole reduced the parasite infective fitness.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The combined therapy group, Bz25/AMD50, received 25 mg Bz/kg/day plus 50 mg AMD/kg/day. The dose of 25 Bz mg/kg is well established as a suboptimal dose ( 60 ), which corresponds to a one-quarter Bz optimal dose (100 mg Bz/kg/day) ( 63 ). A dose of 50 mg/kg/day of AMD was chosen based on the estimated body surface area of mice and the average body surface area of an adult human and is considered equivalent to the clinical dosage for an adult human (300 mg/kg/day) ( 64 ).…”
Section: Methodsmentioning
confidence: 99%